ШАЙХ АКБАР(УЛУҒ ШАЙХ)НИНГ ДИНИЙ-ФАЛСАФИЙ МЕРОСИГА БИР НАЗАР (Scientific journal of the Fergana State University, 2023)
In this article, sufistic and philosophical heritage of Shayx Akbar, one of the most outstanding scientist of the Eastern philosophy of the Middle Ages, is stated